Recuperação de metais a partir da lama vermelha - Aguirre, Marcos (Universidade Federal de São Carlos, 2015)
This paper describes an integrated process for recovering aluminum, iron, titanium, sodium and silica from red mud through a hydrometallurgical treatment sequence. The disposal of red mud, which is the largest waste produced by the aluminum industry, causes considerable environmental problems, and impacts costs greatly. This work presents a proposal to deal with it. Firstly, red mud is subjected to calcination at the 500-600°C range (thermal activation) so as to modify the structure of the metals present in red mud and make the attack with sulfuric acid easier. Next, the red mud is mixed with sulfuric acid and calcinated at 250- 300 °C (acid calcination). After digestion, the metal sulfates in the cake are dissolved by leaching with water and separated from the silica by filtration . Two routes to recuperate the leached metals are presented here, and the second one is analyzed economically. In this second method, silica is separated by filtration and all other metals in the leached solution are precipitated through a hydrometallurgical process in the form of their oxides. The remaining products present high purity level, thus being more easily marketed.
Reclamation of metals from red mud
Keywords: Engenharia química; Lama vermelha; Bauxita; Ativação térmica; Calcinação (Metalurgia); Engenharia econômica; Red mud; Bauxite; Sulfuric baking; Thermal activation; Environmental; ENGENHARIAS::ENGENHARIA QUIMICA